2012
DOI: 10.1016/j.cmet.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission Triggered by Hyperglycemia Is Mediated by ROCK1 Activation in Podocytes and Endothelial Cells

Abstract: SUMMARY Several lines of evidence suggest that mitochondrial dysfunction plays a critical role in the pathogenesis of microvascular complications of diabetes, including diabetic nephropathy. However, the signaling pathways by which hyperglycemia leads to mitochondrial dysfunction are not fully understood. Here we examined the role of Rho-associated coiled-coil containing protein kinase 1 (ROCK1) on mitochondrial dynamics by generating two diabetic mouse models with targeted deletions of ROCK1, and an inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
422
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(446 citation statements)
references
References 38 publications
20
422
3
1
Order By: Relevance
“…A few reports have indicated a pivotal role of mitochondrial dynamics in the homeostasis of different kidney cells during DKD and AKI. 8,28 However, autophagy is believed to exert a cytoprotective effect during kidney injury, such as in AKI, DKD, and obesity, where the basal rate of autophagy may increase initially but because of its relative decrease, subsequently, the podocytes and tubular cells get readily damaged. [33][34][35][36] In addition, elimination of damaged mitochondria by mitophagy was reported to be relatively deficient or decreased in the cardiac musculature of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few reports have indicated a pivotal role of mitochondrial dynamics in the homeostasis of different kidney cells during DKD and AKI. 8,28 However, autophagy is believed to exert a cytoprotective effect during kidney injury, such as in AKI, DKD, and obesity, where the basal rate of autophagy may increase initially but because of its relative decrease, subsequently, the podocytes and tubular cells get readily damaged. [33][34][35][36] In addition, elimination of damaged mitochondria by mitophagy was reported to be relatively deficient or decreased in the cardiac musculature of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although the pathogenesis of DKD still remains unclear, recent studies in animals and humans have led to an emerging concept that mitochondrial dysfunctions, which are pivotal events, lead to activation of various cellular processes and aberrant signaling in different cell types of the kidney. [7][8][9] Mitochondria are dynamic organelles that constantly undergo fusion and fission cycles to maintain a balance of cellular reticular network and mitochondrial turnover. 10 Their dynamics are regulated by profission proteins (Drp1 and Fis1) and profusion mediators (Mfn1/2 and OPA1).…”
mentioning
confidence: 99%
“…DN is a leading cause of end-stage renal disease, and alterations in mitochondrial bioenergetics and dynamics in the kidney in experimental diabetes have been documented (4,37,38). Hence, we superimposed diabetes onto AIF knockdown in mice to determine whether the renal phenotype could be worsened.…”
Section: Superimposition Of Diabetes On Aifm1 Knockdown Worsens Kidnementioning
confidence: 99%
“…29 In addition, diabetic mouse models and in vitro studies have demonstrated that hyperglycemia induced mitochondrial fragmentation in podocytes, endothelial cells, and renal tubular cells. 7,30 Finally, WBCs are involved in the kidney's response to injury as evidenced by leukocyte infiltration in kidney tissues of patients with CKD and in experimental models. [31][32][33] Lower mtDNA copy number might alter the role of WBCs and platelets in injury response.…”
Section: Main Findingsmentioning
confidence: 99%